Validation of the guidelines for sustainable construction of Industrialized Building System (IBS) - Yunus, Riduan; Trigunarsyah, Bambang; Abdul Hamid, Abdul Rahim; Mohammad Afandi, Syamsul Herman; Mehdi Riazi, Salman Riazi (Horizon Research Publishing Co., Ltd., 2023)
Validation of developed guidelines is vital to ensure their applicability and accuracy in responding to real scenarios within the local context. A case study was adopted in this research to assess the application of developed guidelines in a real scenario that improves sustainability for Industrialized Building System (IBS) projects. This process ensures the significance of the guidelines as a decision tool in promoting sustainability. Every process and procedure was validated to ensure the guidelines could be used in the actual projects. It is important to demonstrate on advantages and benefits of the guidelines to explicitly assist the design team in making the best decision. There are five criteria in selecting the appropriate case projects, namely 1) location, 2) information accessibility, 3) method of construction, 4) high-impact projects for the community and 5) IBS Score. Only non-residential buildings were selected in this study. This study's two data collection methods are semi-structured interviews and documents review. Eleven (11) respondents from the management team were selected to participate in the interviews. The results show that the respondents confirmed that the guidelines appropriately apply in the construction industry. Similar results were achieved, and sustainability was improved in the selected projects. All participants' comments and recommendations were synthesised to improve the project outputs. Accordingly, improved guidelines were developed that significantly improved the sustainable deliverables of IBS applications.